A new non-sexually dichromatic species of the genus Gonatodes (Sauria: Sphaerodactylidae) from Sierra de Perijá, Venezuela - Rojas-Runjaic, Fernando J. M.; Infante-Rivero, Edwin E.; Cabello, Pedro; Velozo, Pablo (Zootaxa, 2010)
A new species of diurnal gecko of the genus Gonatodes is described from Sierra de Perijá in western Venezuela. The new species is the only member of the genus lacking sexual dichromatism, and can be readily distinguished from all congeners by the unique combination of the following characters: medium body size; supraciliary spine absent; dorsolateral light spots coinciding with clusters of enlarged, conical to spinelike scales; males with escutcheon area on belly and undersurface of thighs; unique subcaudal scale pattern (1’2” followed by 1’1”); and both sexes with cryptic dorsal color pattern. The new species increases the number of Gonatodes known from Venezuela to 17.